Analysis of the Abundance and Morphological Characteristics of Airborne Microorganisms in an Environmental Engineering Laboratory - Diah Ayu Prawitasari; Rina Isnikarita; Annisa Nur Lathifa; Suphia Rahmawati (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to analyze the abundance and morphology of airborne microorganisms in the Environmental Engineering Laboratory and to relate their distribution to differences in room conditions and sampling time. Sampling was conducted in two rooms, Room A and Room B, during the morning and afternoon using a microbiological air sampler with Nutrient Agar (NA), Potato Dextrose Agar (PDA), and Plate Count Agar (PCA) media. Statistical analysis showed that room conditions strongly influenced the distribution of airborne microorganisms and were also affected by indoor airflow patterns. The findings revealed higher concentrations in Room B than in Room A (morning averages: 60.75 vs. 23.75 CFU/m³; afternoon averages: 44.5 vs. 24.25 CFU/m³), with a statistically significant difference (Mann–Whitney, p-value < 0.05). These results indicate that optimizing airflow direction, scheduling cleaning activities, and conducting routine bioaerosol monitoring are necessary as indicators of control performance. Morphological analysis identified Gram-positive bacteria such as Staphylococcus and Bacillus, as well as fungi such as Aspergillus and Trichoderma, all of which may affect health and indoor air quality. This study underscores the importance of laboratory indoor air quality management in reducing health risks associated with airborne microorganisms.